2022
DOI: 10.1186/s12903-022-02685-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring challenges and mitigation strategies towards practicing Teledentistry

Abstract: Background Since the beginning of the COVID-19 pandemic, many dentists have opted for Teledentistry as a mechanism for patient consultation, oral lesion evaluation, diagnosis, and monitoring. The current study explores the challenges faced and potential solutions proposed by dentists practicing Teledentistry in a developing country like Pakistan. Methods A qualitative case study was carried out from January to December 2021. A purposive maximum var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The majority were conducted either in the United States of America (n = 5) [19–23; India (n = 4) [ 19 22 ]; or Canada (n = 2) [ 12 , 23 ]. Studies were also conducted in Rumania [ 1 ]; Chile [ 24 ]; Pakistan [ 25 ]; and South Africa [ 26 ]. Additionally, two studies included multiple countries [ 13 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority were conducted either in the United States of America (n = 5) [19–23; India (n = 4) [ 19 22 ]; or Canada (n = 2) [ 12 , 23 ]. Studies were also conducted in Rumania [ 1 ]; Chile [ 24 ]; Pakistan [ 25 ]; and South Africa [ 26 ]. Additionally, two studies included multiple countries [ 13 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“… Access, and delivery of telemedicine applications in dentistry and medicine should be expanded and improved to provide access to all population groups. Fahim et al, 2022 [ 25 ] Pakistan Not explicit Challenges and solutions for teledentistry in Pakistan Government should encourage teledentistry and reduce barriers to implement teledentistry . Stakeholders should be included in the development of guidelines and regulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for this might be that TD requires a stable network as well as technological and security support to get started, yet there is very little published evidence regarding the estimated set-up costs for teledentistry. According to a study that was conducted to explore the challenges and mitigation strategies towards practicing TD, the set up costs were one of the challenges for establishing TD in a private dental office because practitioners may have to pay for it themselves, with few financial benefits [ 21 ]. However, our study results contrasted among dental professionals in Pakistan and Saudi Arabia in a survey, which reported that the least number of participants agreed that TD would be too expensive to set up [ 22 ].…”
Section: Discussionmentioning
confidence: 99%